The Independent Directors in Malaysia: The Analysis of the Legal Requirements for Conventional and Shariah Business Companies - Kamaliah, Salleh; Noor ‘Ashikin, Hamid; Noraida, Harun; Asiah, Bidin; Zuhairah Ariff, Abd Ghadas (2017)
The severity of the concept of independent directors in Malaysia is reflected through the introduction of corporate governance in this country. Although both Acts 125 and 777 are silent on the provision for independent director, the emphasis of the need for independent director to exist within the board composition can be seen in the Bursa Malaysia Listing Requirements (‘LR’) and the Malaysian Code on Corporate Governance (‘MCCG’). This paper will examine the basis and the significance of their existence in decision making process through board meeting, which commonly takes place in companies running conventional or Shariah compliance businesses. The method used in this study is analysis of the LR and MCCG provisions and reported cases. The analysis revealed that the independent directors carry substantial obligations by ensuring effective functions of the board which reflects good corporate governance within the company.